ENVIRONMENTAL ACCOUNTING ANALYSIS ON WASTE MANAGEMENT IN BALONGSARI PUBLIC HEALTH CENTER KARAWANG - Shabira, Adella Haifa; Lasmini, Lilis; Septiawati, Rohma (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This study aims to analyze the implementation of environmental accounting in waste management at the Balongsari Health Center in Karawang. The method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results show that the Balongsari Health Center has incurred costs for managing medical and non-medical waste but has not specifically categorized environmental costs in its financial reports. The conclusion is that the implementation of environmental accounting at Balongsari Health Center is still limited, and waste management is conducted according to standard procedures, although not fully optimal due to facility limitations such as the absence of an IPAL (Wastewater Treatment Plant).